Analysis from the classical test theory and item response theory of the Satisfaction with Life Scale (SWLS) in an Ecuadorian and Colombian sample (2024)
Verify the measurement equivalence by nationality (Colombia and Ecuador), internal consistency, and discrimination and difficulty from the Item Response Theory of the Satisfaction with Life Scale. Instrumental study based on Classical Test Theory (CTT) and Item Response Theory (IRT). 464 university students, 217 of Colombian (54.4% women, mean age = 20.9 years, SD = 3.4), and 250 Ecuadorian (60% women, mean age = 21 years, SD = 2.0). The SWLS presented a single-factor model for both the Colombian and Ecuadorian samples. In addition, the instrument presented measurement equivalence between countries at the metric level and has adequate internal consistency according to the CTT criteria. Finally, regarding the IRT criteria, the items present adequate discrimination and difficulty. The SWLS presents evidence of cross-cultural invariance in addition to having new properties based on the IRT that have not been fully investigated before.